Depressive symptoms in patients with coronary artery disease - Débora Maria Mendonça da Cunha; Thaynara Silva dos Anjos; Cristiane Franca Lisboa Gois; Maria Cláudia Tavares de Mattos; Luísa Vale Carvalho; Jones de Carvalho; Flávio Aragão Silva; Débora Almeida Silveira Sobral; Kamila de Mendonça Fialho; Eliana Ofélia Llapa Rodriguez
Objective.To assess the presence of depressive symptoms in patients with coronary artery disease in the preoperative period for coronary artery bypass surgery (CABG) in Aracaju, Sergipe, Brazil. Methods. A cross-sectional study with 63 hospitalized patients prior to CABG. Two instruments were used for data collection; one for the sociodemographic and clinical characteristics, and the other to evaluate the presence of depressive symptoms, Beck Depression Inventory (BDI). Results. The mean age was 58 years; most were male (60.3%); with a partner (81%) low educational level (71.4% attended school through elementary school). Among the patients, 36.5% were classified with dysphoria, and 25.4% had some degree of depression (6.3% mild, 17.5% moderate, and 1.6% severe). The group of patients with lower educational level presented higher depressive symptoms. Conclusion. Six of every ten patients with coronary artery disease showed dysphoria or some degree of depression. The results of this study can support the planning of nursing care for patients before and after CABG, as well as the development of public health policies to ensure complete, quality care for these patients, understanding depression as a variable that can interfere with recovery after cardiac surgery.